(untitled) (AYUSHDHARA, 2024)
Cervical erosion is a condition where the squamous epithelium of the ectocervix is replaced by columnar epithelium which is continuous with endocervix. This condition can be taken as Karnini Yonivyapada. In cervical erosion, the cervix becomes hypertrophic, clogged, and covered with small red projections that resemble sprouts. Due to this clinical appearance, Karnini Yonivyapada is likened to cervical erosion. The treatment aim to eliminate the ectopic columnar epithelium and create a healthy cellular environment, ensuring proper regression of the erosion. In the present study the complaints of patient was white discharge per vaginally with itching since 1 year associated with backache. In ’Karnini yonivyapada’, the imbalanced Doshas are Vata and Kapha, and the affected Dhatu is Rakta. So the treatment principle adopted was balancing Vata and Kapha with purification of Rakta. The condition was treated with Kshara karma through Tuttak drava. Tuttak drava was prepared as aqueous solution of copper sulphate and is used because of Vranaghna, Vranadoshahara properties.